Determinan Underpricing Pada Perusahaan Non Keuangan yang Melakukan Initial Public Offering di Bursa Efek Indonesia Tahun 2017-2022 - Nata Arnetha Nababan; Esti Damayanti (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
This research was conducted on non-financial companies conducting Initial Public Offering (IPOs) on the Indonesia Stock Exchange (IDX) during the 2017-2020 period. The research method employed was a comparative causal quantitative study using secondary data obtained from the Indonesia Stock Exchange. The sample determination method employed a purposive sampling approach, resulting in a total of 134 companies experiencing underpricing out of 305 companies that conducted IPOs between 2017 and 2020. Based on the results of the research analysis, it can be seen that financial leverage and earnings per share have a positive effect on underpricing, while company age and ROE do not affect underpricing. By understanding the dynamics of underpricing, it is hoped that investors can better manage risk and become a consideration for potential investors in making investment decisions. By considering the factors that influence underpricing in initial public offering, more profitable investment opportunities can be identified